Deficiência e autodeterminação humana: compaixão e insensibilidade no caso Vincent Humbert Human handicap and self-determination: compassion and insensibility in the Vincent Humbert case - Ray Pereira (História, Ciências, Saúde: Manguinhos, 2007)
Discute a questão da autodeterminação de pessoas com deficiência, sem comprometimento das funções cognitivas. Traz como pano de fundo a história de Vincent Humbert, francês de 22 anos que ficou tetraplégico, cego e mudo após um acidente automobilístico. O sofrimento intenso do rapaz durou vários meses, resultando em insistente pedido de eutanásia aos médicos e à sua mãe. A morte de Humbert, após uma tentativa frustrada de eutanásia praticada pela mãe, reabre a polêmica em torno da eutanásia e do suicídio assistido. Partindo desse contexto, apresenta aspectos históricos da deficiência e analisa criticamente a autonomia e a eutanásia de Humbert. This work has the objective of discussing human self-determination among handicapped people with unaffected cognitive functions. The background for the article is the history of 22 year-old Vincent Humbert, who became tetraplegic, blind and speech-impaired after a car accident. The young man intense suffering lasted for several months and resulted in an insistent request for euthanasia to his mother. Humbert's death, after his mother's unsuccessful effort to conduct the euthanasia, restates the polemics concerning euthanasia and assisted suicide. In this context, the article presents historical aspects of human handicap and critically analyzes Humbert's autonomy and euthanasia.